Gender Differences in Strategic Reasoning - Marcus Dittrich; Kristina Leipold (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies gender differences in strategic situations. In two experimental guessing games - the beauty contest and the 11-20 money request game - we analyze the depth of strategic reasoning of women and men. We use unique data from an internet experiment with more than 1,000 participants. We find that men, on average, perform more steps of reasoning than women. Our results also suggest that women behave more consistently across both games.
Keywords: C72; C90; J16; 330; gender differences; strategic reasoning; level-k; beauty contest; 11-20 money request game